GLP-1's role in neuroprotection: a systematic review. (12th May 2019) - Erbil, Damla; Eren, Candan Yasemin; Demirel, Cağrı; Küçüker, Mehmet Utku; Solaroğlu, Ihsan; Eser, Hale Yapıcı
ABSTRACT: Glucagon-like peptide 1 (GLP-1) is a target for treatment of diabetes; however, its function in the brain is not well studied. In this systematic review, we aimed to analyze the neuroprotective role of GLP-1 and its defined mechanisms. Methods : We searched 'Web of Science' and 'Pubmed' to identify relevant studies using GLP-1 as the keyword. Two hundred and eighty-nine clinical and preclinical studies have been included. Data have been presented by grouping neurodegenerative, neurovascular and specific cell culture models. Results : Recent literature shows that GLP-1 and its agonists, DPP-4 inhibitors and combined GLP-1/GIP molecules are effective in partially or fully reversing the effects of neurotoxic compounds, neurovascular complications of diabetes, neuropathological changes related with Alzheimer's disease, Parkinson's disease or vascular occlusion. Possible mechanisms that provide neuroprotection are enhancing the viability of the neurons and restoring neurite outgrowth by increased neurotrophic factors, increasing subventricular zone progenitor cells, decreasing apoptosis, decreasing the level of pro-inflammatory factors, and strengthening blood-brain barrier. Conclusion : Based on the preclinical studies, GLP-1 modifying agents are promising targets for neuroprotection. On the other hand, the number of clinical studies that investigate GLP-1 as a treatment is low and further clinical trials are needed for a benchside to bedside translation of recent findings.